VD_FINDINFO Jug / 2017 / 354 vom 7. April 2017 - VD Tribunal cantonal (2017)
FIXATION DE LA PEINE, APPRÉCIATION DES PREUVES, VIOL, INTERNEMENTDROIT PÉNAL | 49 CO, 190 CP, 47 CP, 64 al. 1 CP, 10 CPP (CH)